PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES SEBAGAI LITERASI DIGITAL DAN APRESIASI SENI MURID DI SMA PEMBANGUNAN LABORATORIUM UNP - Bayu Dimas Saputra; Ardipal; Indrayuda; Jupriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a Google Sites-based learning media as a platform to enhance students’ digital literacy and artistic appreciation in Cultural Arts learning at SMA Pembangunan Laboratorium UNP. The research was motivated by the limited utilization of digital technology in learning activities, low student engagement in independent learning, and the absence of digital media that facilitates the appreciation of students’ artworks. This study employed a Research and Development (R&D) approach using the 4D development model, consisting of Define, Design, Develop, and Disseminate stages. Research instruments included expert validation sheets, practicality questionnaires for teachers and students, and learning effectiveness tests. The findings revealed that the Google Sites-based learning media achieved a “very valid” category based on evaluations from media experts, material experts, and language experts. The practicality test results showed percentages of 93% from teachers and 89% from students, indicating that the media was “very practical.” The effectiveness test demonstrated that the learning media was sufficiently effective in Cultural Arts learning, with most students achieving learning outcomes in the good and satisfactory categories. In addition to serving as a digital learning platform, Google Sites functioned as a medium for artistic appreciation through a virtual art exhibition feature that encouraged creativity, self-confidence, and active student participation in the learning process. Therefore, the Google Sites-based learning media was found to be valid, practical, and effective in supporting students’ digital literacy and artistic appreciation at SMA Pembangunan Laboratorium UNP.